Theoretical nuclear physics in Italy : proceedings of the 11th Conference on Problems in Theoretical Nuclear Physics : Cortona, Italy, 11-14 October 2006 - Covello, A. (Aldo) (World Scientific, 2007)
This volume gives a comprehensive overview of the latest research activity undertaken in the field of theoretical nuclear physics in Italy. Several topics of current interest are included: from nuclear matter and nuclear structure to nuclear astrophysics and quark?gluon plasma.
Keywords: Nuclear physics -- Congresses.; Nuclear physics -- Research -- Italy -- Congresses.; Physique nucléaire -- Congrès.; Physique nucléaire -- Recherche -- Italie -- Congrès.; SCIENCE -- Physics -- Nuclear.; SCIENCE -- Physics -- Atomic & Molecular.; Nuclear physics; Nuclear physics -- Research; Italy; Conference papers and proceedings